Modeling the Evolution and Propagation of 10 September 2017 CMEs and SEPs Arriving at Mars Constrained by Remote Sensing and In Situ Measurement. Issue 8 (30th August 2018) - Guo, Jingnan; Dumbović, Mateja; Wimmer‐Schweingruber, Robert F.; Temmer, Manuela; Lohf, Henning; Wang, Yuming; Veronig, Astrid; Hassler, Donald M.; Mays, Leila M.; Zeitlin, Cary; Ehresmann, Bent; Witasse, Olivier; et al.
Abstract: On 10 September 2017, solar energetic particles originating from the active region 12673 produced a ground level enhancement at Earth. The ground level enhancement on the surface of Mars, 160 longitudinally east of Earth, observed by the Radiation Assessment Detector (RAD) was the largest since the landing of the Curiosity rover in August 2012. Based on multipoint coronagraph images and the Graduated Cylindrical Shell model, we identify the initial 3‐D kinematics of an extremely fast coronal mass ejection (CME) and its shock front, as well as another two CMEs launched hours earlier with moderate speeds. The three CMEs interacted as they propagated outward into the heliosphere and merged into a complex interplanetary CME (ICME). The arrival of the shock and ICME at Mars caused a very significant Forbush decrease seen by RAD only a few hours later than that at Earth, which was about 0.5 AU closer to the Sun. We investigate the propagation of the three CMEs and the merged ICME together with the shock, using the drag‐based model and the WSA‐ENLIL plus cone model constrained by the in situ observations. The synergistic study of the ICME and solar energetic particle arrivals at Earth and Mars suggests that to better predict potentially hazardous space weather impacts at Earth and other heliospheric locations for human exploration missions, it is essential to analyze (1) the eruption of the flare and CME at the Sun, (2) the CME kinematics, especially during their interactions, and (3) the spatially and temporally varying heliospheric conditions, such as the evolution and propagation of the stream interaction regions. Plain Language Summary: From 4 to 6 September 2017, heliospheric activity suddenly and drastically increased starting from a simple sunspot which transformed into a complex region with four X‐class flares accompanied by several Earth‐directed magnetic clouds and shocks driven by them. Only a few days later, on 10 September 2017 starting at about 15:53, the same region launched another extremely fast magnetic cloud accompanied by an intense shock, which spread rapidly across the entire solar surface. Ten to 20 min later, particles accelerated at the Sun arrived at Earth, some of them with enough energy to reach Earth's surface and caused a ground level enhancement of radiation. A few hours later and shortly before 20:00, the Radiation Assessment Detector observed the biggest event since the landing of the Curiosity rover in August 2012 on the surface of Mars which was about 160 degrees east from Earth in the heliosphere. This was the first solar energetic particle event seen at ground level on the surface of two planets. Some particles were also transported across magnetic field lines throughout the heliosphere and were detected at the back side of the Sun where the eruption was centered. Meantime, the intense and wide shock also propagated into the interplanetary space, reached Earth on its west edge ∼50.5hr after launch and hit Mars on its east flank ∼59hr after launch, causing the biggest depression of the galactic cosmic ray flux measured by Radiation Assessment Detector on Mars. We analyzed this event starting from the flare and particle acceleration at the solar surface. Constrained by in situ observations at both planets, we observed and modeled the eruptions, solar energetic particles, magnetic clouds, and their shock fronts from the Sun into interplanetary space and all the way to Mars and Earth. Key Points: The 10 September 2017 SEP event was the first GLE observed on the surface of two different planets: Earth and Mars The SEP and ICME impact on Mars is helping us better understand extreme space weather conditions at Mars Synergistic modeling of the ICME and SEP propagation advances our understanding of such complex events for improved space weather forcasts